La réception d’un savoir de l’attention dans les contes merveilleux - Renaud Hétier (Éducation et Socialisation)
Two major difficulties can be drawn out, in education and in training, in terms of paying attention. First of all, capture and focus the attention on objects of knowledge and objects of culture, on the other hand, pay attention to others, take care of others. But, it may be the separation of these two forms of attention that could cause problems. In this case, a cultural device, such as contagion, which makes the attention, converge to "something" and the attention, to someone, an expositive that takes care of him or her - the auditor - whose attention is requested and can be inspiring. The quality of this convergence will be highlighted by the presentation of an amazing story. From this description, it is the pedagogy in general that can be interrogated, in its ability to create experience and functional spaces in which people of different natures can be met and approved, there suspended life, being both virtual and functional at the same time, while giving us all their attention, our own capacity to give them both life and take care of them.